Strengthening civic engagement of the bukit raya village community through the one thousanda a day donation activity (s3) - Andriani, Tutik; Lutfiana, Rose Fitria; Wibowo, Arif Prasetyo (Jurnal Pendidikan PKN (Pancasila dan Kewarganegaraan), 2025)
Civic engagement is an important part of building an active and empowered society. However, community participation in social and political matters, especially at the village level, is still relatively low. This study aims to explain the implementation of Thousand Days Alms (S3) activities in Bukit Raya Village, assess the impact of Thousand Days Alms (S3) activities on increasing Civic Engagement of the Bukit Raya Village community, and to recognize the factors that support and hinder the strengthening of Civic Engagement through the Thousand Days Alms (S3) program in Bukit Raya Village. This program is a local initiative based on local wisdom and aims to increase solidarity and social concern, with a daily contribution of Rp1,000,-. For this study, a descriptive qualitative method was used, by collecting data through observation, interviews, and documentation in Bukit Raya Village, East Kalimantan. The informants in this study consisted of program managers, community leaders, local residents, and beneficiaries